Coronary surgery in patients with low ejection fraction: mid-term results. (April 2013) - Ergüneş, Kazim; Yurekli, Ismail; Lafcı, Banu; Gokalp, Orhan; Akyuz, Muhammed; Yetkin, Ufuk; Yilik, Levent; Gurbuz, Ali
Background: The aim of this study was to investigate the effect of preoperative low ejection fraction (≤30%) on postoperative morbidity and mortality in patients undergoing isolated on-pump coronary artery bypass grafting. We also investigated the effect of pre- and perioperative factors on survival. Methods: Between January 2002 and December 2009, 103 (6.2%) patients with an ejection fraction ≤30% and 1554 (93.8%) with an ejection fraction >30% underwent coronary artery bypass grafting. Results: In multivariate logistic regression analysis, cardiopulmonary bypass time, operation time, prolonged inotropic support, and intensive care unit stay were independent predictors of mortality in patients with low ejection fraction. Intensive care unit and hospital stays were significantly longer in these patients, and the postoperative mortality rate was significantly higher. Advanced age (≥70 years) influenced mortality during the follow-up of patients with low ejection fraction. Midterm survival was significantly reduced in patients with ejection fraction ≤30%. Smoking, prolonged inotropic support, and prolonged ventilatory support were independent predictors of midterm survival in patients with ejection fraction ≤30%. Conclusion: On-pump coronary artery bypass grafting can be performed in patients with ejection fraction ≤30%, with reasonable mortality and morbidity rates.